Pickeringite from the Pieprzowe Mts. (the Holy Cross Mts. Central Poland) - Naglik, Beata; Natkaniec-Nowak, Lucyna (Geology, Geophysics and Environment, 2015)
Pickeringite (MgAl2(SO4)4 *22 H2O) associated with another sulphates (alunogene, epsomite) was found as an efflorescence mineral within the weathering zone of the Pieprzowe Mts. shale formation (the Holy Cross Mts., Central Poland).